2021
DOI: 10.3343/alm.2021.41.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnostic Methods for Clostridioides difficile Infection: the First Systematic Review and Meta-analysis in Korea

Abstract: Background Various methods are used for the diagnosis of Clostridioides difficile infection (CDI). We systematically analyzed and investigated the performance of current laboratory diagnostic methods for CDI. Methods We performed systematic review and meta-analysis of studies in PubMed, Web of Science, Cochrane Library, and KoreaMed. The following methods were evaluated glutamate dehydrogenase (GDH) enzyme immunoassays (GDH EIAs), toxin A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(24 reference statements)
1
4
0
Order By: Relevance
“… 10 The perception of sensitivity and specificity of NAAT was mostly positive, suggesting that the specialists were quite satisfied, consistent with the fact that sensitivity and specificity of NAAT are known to be remarkable. 5 10 The relatively lower specificity of C. difficile culture encountered by some could be due to the characteristics of the culture containing non-specific bacteria with a specificity of 60–80%. Perceptions on the sensitivity of GDH was relatively positive, which was lower than NAAT but higher than toxin AB EIA, and that on the specificity led to lower satisfaction compared to NAAT and toxin AB EIA.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“… 10 The perception of sensitivity and specificity of NAAT was mostly positive, suggesting that the specialists were quite satisfied, consistent with the fact that sensitivity and specificity of NAAT are known to be remarkable. 5 10 The relatively lower specificity of C. difficile culture encountered by some could be due to the characteristics of the culture containing non-specific bacteria with a specificity of 60–80%. Perceptions on the sensitivity of GDH was relatively positive, which was lower than NAAT but higher than toxin AB EIA, and that on the specificity led to lower satisfaction compared to NAAT and toxin AB EIA.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to culture, GDH can detect the presence of C. difficile regardless of toxin production, and it is thought to replace the C. difficile culture, as it can detect C. difficile with a sensitivity of 90% or more. 10 The most commonly used culture kit is ChromeID Agar (bioMérieux, Marcy-l'Étoile, France), which was the most commonly used in the 2015 survey as well, and it is preferred since it can screen the C. difficile colony relatively well with color reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 nucleic acid amplification tests may detect asymptomatic carriage due to possible non-expression of the toxin encoding gene and therefore the clinical specificity may be lower than reported. 24 In their meta-analysis conducted in 2019, Kraft et al reported an estimated sensitivity of 94% and a specificity of 97% when NAATs were compared to either cell culture neutralisation assay or TC or both in studies where it was specifically stated that stools were only included if conforming to the shape of the container. 10 …”
Section: Discussionmentioning
confidence: 99%